1512. Variation in Outpatient Urine Testing Practices for Uncomplicated Urinary Tract Infections. (26th November 2018) - Liu, Sonya; Bongu, Jahnavi; Keller, Matthew; Butler, Anne M; Olsen, Margaret A; Durkin, Michael J
Abstract: Background: Urinary tract infections (UTIs) are common in outpatient settings. Evidence-based recommendations suggest empiric treatment of healthy female patients presenting with two or more classic symptoms of UTIs, rather than urine testing. It is unknown how often urine testing is ordered in the community, and if there are opportunities to reduce the number of unnecessary urine tests. This study aims to describe urine testing practices for uncomplicated UTIs in outpatient settings. Methods: Using the 2009–2013 Truven Health Analytics MarketScan database, we extracted outpatient claims data for premenopausal, nonpregnant women aged 18–44 years who met criteria for an uncomplicated UTI or cystitis with antibiotic prescribed ±5 days of diagnosis. Women with recent infections, hospitalizations, urologic abnormalities, diabetes, chronic kidney disease, immune compromise, or other complicating factors were excluded. Urine laboratory tests coded within ±5 days of index UTI were identified. To explore variation in urine testing practices, we compared frequencies of urine testing types according to patient age, region, provider type, testing location, residence in a metropolitan statistical area (MSA), and office visit using Chi-square tests. Results: Of 669, 892 eligible patients with an uncomplicated UTI, 584, 863 (87%) received at least one urine test. Of the patients who received at least one test, 285, 639 (49%) patients received both a urinalysis (UA) and culture, 247, 740 (42%) received a UA only, and 51, 484 (9%) received culture only. Significant variation in testing was observed by patient age, region, provider type, testing location, and office visit (Table 1). Patients in the Northeast and in urban locations more frequently received both a UA and culture. Patients who received both UA and culture were more likely to have been seen by an OB/GYN, whereas patients treated empirically without testing were more likely to have been seen by emergency physicians. Conclusion: In contrast to evidence-based recommendations, the vast majority of patients with uncomplicated UTI received at least one urine test. We observed variation in urine testing practices, which suggests that diagnostic testing stewardship opportunities exist for outpatients with UTIs. Disclosures: All authors: No reported disclosures.